Vulnerability to Alzheimer's pathology in neocortex: The roles of plasticity and columnar organization - Esiri, M; Chance, SA (2006)
Two principal findings in the Pearson et al. paper [73] are commented on here. The first is the regional selectivity within the cerebrum of neurofibrillary tangle (NFT) formation in Alzheimer's disease (AD) which targets association cortex and the primary olfactory cortex alone among regions of primary sensory cortex. The second finding is the clustering of NFT in columns of supra- and infra-granular layers of association cortex. We review recent evidence confirming these findings and comment on their possible significance. We consider that the most attractive hypothesis to explain the vulnerability of the olfactory system and association cortex is the persistent neural plasticity of these regions. On this basis there would be no need to postulate a progressive spreading process. The columnar distribution of clustered NFT can be well understood in the context of recent concepts of columnar organization of the cerebral cortex. The original interpretation that this distribution of NFT reflects pathology in neurons subserving cortico-cortical and cortico-subcortical connections seems to us to have stood the test of time. © 2006 - IOS Press and the authors. All rights reserved.